Conspiracy Against the Public – An Experiment on Collusion - Åshild A. Johnsen; Ola Kvaløy (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study to what extent collusive behavior is affected by the awareness of negative externalities. Theories of outcome-based social preferences suggest that negative externalities make collusion harder to sustain than predicted by standard economic theory, while sociological theories of social ties and intergroup comparisons suggest that bilateral cooperation can be strengthened if there exist outsiders that gain from cooperative break down. We investigate this in a laboratory experiment. Subjects play the infinitely repeated prisoner's dilemma with and without a negative externality. The externality is implemented by letting subjects make a positive contribution to a public good if they choose to defect from cooperation, i.e. cooperation is collusive since the gains are at the expense of the public. We find that this negative externality increases collusive behavior. Subjects cooperate more if it hurts a third party.
Keywords: C91; 330; infinitely repeated prisoner's dilemma game; negative externality; cooperation; collusion; experiment